Development of problem based e-comic on the theme of domestic politics on student learning achievement - Ismiyanti, Yulina; Mayasari, Novi; Nugraheni, Setyo Wuri Kartika (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2024)
In elementary schools, the lack of utilization of learning media and restricted learning tools causes children to become bored and have difficulties grasping the curriculum. This project aims to create problem-based e-comics that are valid, practical, and useful for educational purposes. This research and development project used the ADDIE development paradigm, which includes stages such as analysis, design, development, implementation, and evaluation. Of all the stages completed, the problem-based e-comic generated fits the valid requirements, with a validity percentage of 87% falling into the category of highly viable. Problem-based e-comics also meet practical standards, with instructor response questionnaire analysis yielding an 89% score and student answer questionnaires yielding a 100% score, indicating they are efficiently practical. A learning with problem-based e-comic media is effective for class student learning accomplishment IV SDN-04. Mejobo, the t-test results yielded a 0.00 significant value, indicating a difference in student learning achievement before and after learning using problem-based e-comics. The results of the t-test were strengthened by the results of the normalized gain test, which yielded a value of 0, 63, which falls into the medium group. It is intended that the production of problem-based e-comics will expand the repertory of intellectual property while also serving as a medium and learning resource for elementary school pupils.